PENGARUH KESELAMATAN DAN KESEHATAN KERJA (K3) TERHADAP KINERJA KARYAWAN PT. HALEYORA POWERINDO PEKANBARU - Simanjuntak, Nanda; Andri, Seno (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Working safety show at protection of prosperity of physical with an eye to prevent the happening of accident or injure related/relevant with work, health work to refer at physical condition, bouncing and stability of emotion in general. condition of healthy Health and the goodness will be optimal of performance of than employees and condition of ugly health can bother employees performance, performance basically is what done/conducted or is not done/conducted by a officer. management of Performance is entirety of activity done/conducted to increase the company or organisation performance, inclusive of performance of each individual and working team in the company.This research is done/conducted in this Research is writer do/conduct at PT. Haleyora Powerindo Branch Pekanbaru. As for reason chosen the location choice because of this company active in kelistrikan specially the conservancy which is according to researcher own risk happened by the accident work and fluctuate his/its is performance of employees every year nya.In this research is methodologies used by is quantitative and descriptive with program SPSS, where sampel used by that is entire/all employees of part of field that is as much 70 responder, Enquette (quesioner), representing a[n data collecting givenly or propagate list of pertanyaan/pernyataan to responder on the chance of giving respon for the questionnaire. Interviewing, that is do/conduct Question and answer directly by supervisor, and also the manager becoming research responder.From result analyse data covering validity test, reabilitas, and doubled linear regresi, safety and health work to employees performance. Each owning indicator which each other be interconnected and have an effect on positive to performance of at employees of haleyora Pekanbaru.Keyword: Safety, health work and the employees performance